2011
DOI: 10.4161/auto.7.12.17892
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of p62 in degenerated spinal cord under chronic mechanical compression

Abstract: Intracellular accumulation of altered proteins, including p62 and ubiquitinated proteins, is the basis of most neurodegenerative disorders. The relationship among the accumulation of altered proteins, autophagy, and spinal cord dysfunction by cervical spondylotic myelopathy has not been clarified. We examined the expression of p62 and autophagy markers in the chronically compressed spinal cord of tiptoe-walking Yoshimura mice. In addition, we examined the expression and roles of p62 and autophagy in hypoxic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 61 publications
5
55
2
Order By: Relevance
“…Through LIR motif and UBA domain, p62 interacts with ATG8 family and ubiquitinated proteins which is essential for the formation of autophagosomes and degradation of proteins [8]. However, excessive p62 is harmful as shown by the findings that p62 accumulation was associated with neurodegeneration [12, 13], cancer cell proliferation and migration [11] or podocytes epithelial-to-mesenchymal transition [31]. Similarly, in the present work, by using genetic and pharmacological manipulations, we found that p62 accumulation induced by CD38 gene deficiency or lysosomal dysfunction was a major contributor to the proliferation and dedifferentiation change of CAMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through LIR motif and UBA domain, p62 interacts with ATG8 family and ubiquitinated proteins which is essential for the formation of autophagosomes and degradation of proteins [8]. However, excessive p62 is harmful as shown by the findings that p62 accumulation was associated with neurodegeneration [12, 13], cancer cell proliferation and migration [11] or podocytes epithelial-to-mesenchymal transition [31]. Similarly, in the present work, by using genetic and pharmacological manipulations, we found that p62 accumulation induced by CD38 gene deficiency or lysosomal dysfunction was a major contributor to the proliferation and dedifferentiation change of CAMs.…”
Section: Discussionmentioning
confidence: 99%
“…The p62 mediated selective autophagic clearance of proteins provides an important degradation mechanism, especially when organisms are under the influence of mutation, aging, or environmental stresses [9]. A defect in autophagy may result in an p62 accumulation associated with a host of detrimental effects including rapid tumor growth with adverse prognostic behavior [10], distant metastases [11], neuropathology [12], and neurodegenerative disorders [13]. In the present study, we sought to elucidate whether the p62 accumulation elicited the proliferation and phenotype change of CAMs following autophagy defect induced by CD38 gene deficiency or lysosomal disorder.…”
Section: Introductionmentioning
confidence: 99%
“…3B and F). The rates of tension reduction were 24.9%/mm (r 2 = 0.939) for the mean 20-g baseline, 25.0%/mm (r 2 = 0.959) for the mean 40-g baseline, and 24.9%/mm (r 2 = 0.953) for the mean of the 2 trials within this span.…”
Section: Vertebral Column Resectionmentioning
confidence: 99%
“…While tension previously has been investigated in human cadaveric models of tethered cord syndrome, 8 dural buckling has only been investigated in animal models. 1,16,19,25 We hypothesized that 2 parameters define the boundaries of this region: tension reduction and dural buckling. The primary aim of this study was to better define the range of tension reduction and dural buckling in a human cadaveric model.…”
mentioning
confidence: 99%
“…[2][3][4] In recent years, evidence has indicated that autophagy may play an important role in various spinal disease models, including spinal cord contusion injury, spinal cord hemisection injury, and cervical spondylotic myelopathy. [5][6][7] However, the occurrence and role of autophagy in neural tissues following spinal cord I/R injury have not been clearly illustrated.…”
mentioning
confidence: 99%